NEW TECHNOLOGIES FOR DIDACTICS AND MOTOR EDUCATION - Francesco Peluso Cassese (Giornale italiano di educazione alla salute, sport e didattica inclusiva, 2020)
The investigation on the possible scientific relationships between Motor Activities, Sports and New Technologies in an educational environment still represents a relatively unexplored re- search space. This original field of study, with a view to making the Sport-Technology binomial more efficient, requires, first of all, a complex study of the person and the unexplored potential that characterize it and that technologies can use in an “experimental and innovative” way to favor formative processes. This research horizon, before approaching the different dimensions that can be linked to technologies, movement and sport as educational and didactic resources for All, requires an epistemological reflection that clarifies the ethical value of the individual and the related group of peers both in formal training contexts, which are not formal. The values of Sport, Physical Education and New Technologies constitute an innovative opportunity for the growth of the group and a constant stimulation on the didactic level for the construction, in the School and in All the Formative Systems, of a privileged and multi-experiential space to experiment an alternative learning system and to develop skills and competences too often compressed by the traditional didactics system.